The Religious Studies Aspect of Forensic Evaluation in Cases Involving Offense to Religious Beliefs and Sensibilities - S. N. Astapov (Теория и практика судебной экспертизы)
The paper discusses the phenomenon of offense to religious beliefs and its social and cultural context from the perspective of religious studies. It corroborates the idea that public acts that demonstrate obvious disrespect towards a religion, and “premeditated public desecration” of religious objects lead to distortion of the meaning of religious notions and beliefs, rather than offending religious sensibilities as such. A forensic expert working on cases involving offense to religious beliefs and sensibilities needs to be competent in the field of religious studies in order to address three objectives: to investigate the religious meaning of desecrated objects; to determine the intentional nature of the resulting transformation of religious ideas; and to describe the religious and cultural context and the direction of the transformation, which in turn helps to define the social implications of such transformation.